2019
DOI: 10.26911/thejhpm.2019.04.01.03
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Effect of Community Health Center on Patient Satisfaction of Health Care Service in Ngawi, East Java

Abstract: Background: Perceived patient satisfaction is an important component of health care quality. This study aimed to determine the effect of age, education, income, health financing, quality of health care service, and the contextual effect of community health center on patient satisfaction. Subjects and Method: This was a cross-sectional study conducted in 25 community health centers in Ngawi, East Java, from October to November 2018. A sample of 200 patients was selected by stratified random sampling. The depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…The results of this study are in line with a study conducted by Kurniawan et al (2019) which stated that variations in the characteristics of each community health center have a contextual effect on variations in patient satisfaction (ICC = 13.03%). The contextual effect (accreditation) of each community health center influencing the quality of health services was also stated by Ghareeb et al (2018).…”
Section: The Effect Of Work Environmentsupporting
confidence: 90%
“…The results of this study are in line with a study conducted by Kurniawan et al (2019) which stated that variations in the characteristics of each community health center have a contextual effect on variations in patient satisfaction (ICC = 13.03%). The contextual effect (accreditation) of each community health center influencing the quality of health services was also stated by Ghareeb et al (2018).…”
Section: The Effect Of Work Environmentsupporting
confidence: 90%
“…Study of Kurniawan et al (2019) reported that the age of> 35 years old increased the level of satisfaction by 0.99 times compared to patients <35 years old. The enhancement of age can have an effect on health, which was deterioration in the structure and function of organs, so that older people tend to use health services more than young people.…”
Section: Discussion 1 the Effect Of Age On Patients Satisfactionmentioning
confidence: 96%
“…The components of satisfaction in primary care, such premium payment, information services and membership (16) . The element of a CHSs center was focusing on not only the building condition, comfort of the waiting room and other tangible aspects but also responsiveness, hospitality, and characteristics of patients such as education level, membership of national insurance and condition of CHS (17) . In addition, attitude and behavior of healthcare workers play a pivotal role in supporting tangibility and responsiveness, particularly among chronic disease patients (18) .…”
Section: Across the Social Insurance Administrationmentioning
confidence: 99%
“…Communication means both informing customers in a language they can understand and listening to customers. A company may need to adjust its language for varying needs of its customers (16,17) . Those elements should be implemented in the health services sector; however, being perfect is not easy, and all stakeholders should adopt appropriate approaches to get maximum achievement in healthcare services.…”
Section: Across the Social Insurance Administrationmentioning
confidence: 99%